Formulation of Social Work Criminal Sanctions for Perpetrators of Minor Corruption Crimes Based on Justice - Baktiana, Nur Sari; Hasibuan, Fauzie Yususf; Mulyadi, Lilik (Jurnal Indonesia Sosial Sains, 2024)
In Indonesia, the formulation of criminal sanctions in the Indonesian Criminal Code has progressed, namely the adaptation of the mindset that criminal sanctions do not always have to be punitive. The benchmark of the provisions of Article 85 of the Criminal Code refers to the criteria, measures, and conditions for the imposition of criminal sanctions against social work sanctions for general criminal offenses, while specifically regulating special criminal offenses outside the Criminal Code, for example, Corruption which is regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Corruption. This type of research is normative juridical research with analytical descriptive specifications using the statute approach, case approach, and comparative approach. The data sources in this research are secondary data sources in the form of primary, secondary, and tertiary legal materials. Research data was collected through a literature study using qualitative data analysis techniques. The results showed that there has been a paradigm shift in Law Number 23 Year 2023, which has regulated the existence of social work punishment as one of the main punishments, which previously did not exist in Law Number 1 Year 1946. The ideal formulation so that the application of social work can be applied is by looking at Law Number 31 of 1999 in conjunction with Law Number 21 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Corruption Crimes and must also be able to see the existence of Law Number 1 of 1946, Article 10 of the Criminal Code does not regulate social work.